Differential expression of circRNAs of testes with high and low sperm motility in Yili geese - Wu, Yingping; Li, Haiying; Zhao, Xiaoyu; Baki, Gulnar; Ma, Chen; Yao, Yingying; Li, Jiahui; Yao, Yang; Wang, Lin (Frontiers in Genetics, 2022)
The aim of this study was to explore the potential biological function of circular RNAs (circRNAs) in the sperm motility traits of Xinjiang Yili geese, and to provide a reference for analyzing the mechanism of regulation of Yili geese sperm motility. The 10 selected Xinjiang Yili Geese with high or low sperm motility (five for each group) were 3 years old, with good health, and were kept under the same feeding conditions. Yili geese were slaughtered for the collection of testicular tissue and high-throughput sequencing technology was used to screen differentially expressed circRNAs for bioinformatics analysis. Combined with the previously screened miRNAs related to the sperm motility of Yili geese, the circRNAs miRNAs regulatory network was constructed. The results show that a total of 26,311 circRNAs were obtained from testicular tissues with high and low sperm motility, and 173 DEGs were screened between the two groups (P<0.05, |log2Foldchange|>0), of which 82 were up-regulated and 91 were down-regulated. Functional analysis of the source genes of these DEGs showed that the source genes were mainly involved in biological processes. KEGG enrichment analysis showed that the source genes of DEGs were mainly enriched in autophagy—animal, ubiquinone and other terpenoid-quinone biosynthesis, progesterone-mediated oocyte maturation, regulation of the actin cytoskeleton and other pathways. Furthermore，the visual regulatory network of differential circRNA–miRNA was constructed, including 20 circRNAs and 18 miRNAs, and screened for novel_ circ_ 0017590, novel_ circ_ 0018059, novel_ circ_ 0045314 and another six cores that regulate circRNAs, which target ppy-mir-16, hsa-mir-221-5p, gga-mir-7 and so on. The results suggest that circRNAs may interact with miRNAs to regulate sperm motility in Yili geese, so as to provide a reference for analyzing the molecular mechanism of sperm motility regulation.